TINDAKAN DAN POLA PENGAMBILAN KEPUTUSAN PETANI DALAM PENGENDALIAN DAMPAK ANOMALI IKLIM - Sarjana Sarjana; Meinarti Norma; Seno Basuki (JURNAL LITBANG PROVINSI JAWA TENGAH, 2008)
The importance of farmer’s participation in climate anomaly anticipation and management its impacts are increasingly apparent. The scheme based on the assumption that all strategies need collective action. This study was conducted in order to identify the climate anomaly impacts management of farmer’s level. The study was conducted in eight districts, i.e., Temanggung, Magelang, Kebumen, Brebes, Kendal, Grobogan, Pati, and Sragen, on July – October 2005. The analysis was based on data of structured interview to 84 of farmers, and officers of local agricultural services. Results showed that all farmers stated that El Nino really affected their farming activities. Longer dry season decreased productions, delayed planting season, increased costs of water, planting materials, pesticides, as well as cost in land preparation. At farmers’ level, climate anomaly impacts was managed by planting schedules improvement, changing varieties or commodities, and looking for alternative sources of waters. Farmers determine the actions by considering collective decision and the guidance of agriculture extension workers. Time tolerance limit of farmers for the unpleasant climate was a month. However, most of farmers decided an action faster. As the climate anomaly is an external factor of farming system performance, so government should support the farmer’s collective actions. The supporting schemes include dissemination of the designed strategies to anticipate and manage the impacts climate anomaly, and the supporting facilities to apply the strategies.